11x+2=68
-2 -2
11x=66
/11 /11
X=6
Answer:
The solutions are -0.65 and 4.65.
Step-by-step explanation:
3x^2 - 12x = 9
Divide both sides by 3
x^2 - 4x = 3
To make a square with "x^2 - 4x", you need to have a "+ 4" after it so it can be simplified as (x-2)^2. So add 4 to both sides.
x^2 - 4x + 4 = 7
(x-2)^2 = 7
x - 2 = (square root) of 7
x = 2 (+/-) (square root) of 7.
x = {-0.65, 4.65}
The solutions are -0.65 and 4.65.
hope this helps:)sorry if it doesnt
Answer:
Step-by-step explanation:
7. C
30.D
34.A